ANALISIS LANSKAP PENGARUH GREENERY TERHADAP AGROKLIMAT KOTA BATU MENGGUNAKAN SIG DAN PENGINDERAAN JAUH - Reko, Reko; Budiyono, Debora; Nailufar, Balqis (Fakultas Pertanian, 2019)
Batu City is a division city of Malang Regency, East Java. The status of the administrative city of Batu became Batu City, established since the Decree of the Minister of Home Affairs decreed at the end of October 2001 and began to be active in government activities in 2002. As a tourism-based city, the face of Batu City turned into built-up land. This makes a change in the decline of greenery and agro-climate which affect the decline in the agricultural sector. The purpose of this study is to analyze the differences between greenery and agro-climate in 2003 and 2018 and analyze the relationship between greenery and agro-climate. The method used in this research is descriptive with a qualitative spatial approach. Based on the results of the study showed that, Batu City NDVI in 2003 was dominated by cloud class and NDVI 2018 obtained forest class results. The visible cloud class in 2003 was caused by weather factors during the recording process so that the forest class was covered by the cloud class. In the 2003 LST results which were between 150C-230C and 2018 LST obtained lower results, namely 60C-130C. The changes in greenery and agro-climate and the decrease in temperature are due to atmospheric phenomena namely la-nina (decrease in temperature). Furthermore, based on the correlation test there is a relationship between greenery and agro-climate at a 1% confidence interval between NDVI and LST which is positive and very strong. Kota Batu adalah kota pemekaran dari Kabupaten Malang, Jawa Timur. Status Kota administratif Batu menjadi Kota Batu, ditetapkan sejak turunnya Surat Keputusan Menteri Dalam Negeri pada akhir Oktober 2001 dan mulai aktif dalam kegiatan pemerintahanTahun 2002. Sebagai Kota yang berbasis pariwisata, wajah Kota Batu berubah menjadi lahan terbangun. Hal ini menjadikan perubahan penurunan terhadap greenery dan agroklimat yang berpengaruh pada penurunan sektor pertanian. Tujuan penelitian ini adalah menganalisis perbedaan greenerydan agroklimat Tahun 2003 dan 2018 serta menganalisis hubungan antara greenery dan agroklimat. Metode yang digunakan dalam penelitian ini adalah deskriptif dengan pendekatan spasial kualitatif. Berdasarkan hasil penelitian menunjukan bahwa, NDVI Kota Batu Tahun 2003 didominasi oleh kelas awan dan NDVI 2018 memperoleh hasil kelas hutan. Terlihatnya kelas awan pada Tahun 2003 diakibatkan oleh faktor cuaca pada saat proses perekaman sehingga kelas hutan tertutupi oleh kelas awan. Pada hasil LST Tahun 2003 yaitu antara 150C-230C dan LST Tahun 2018 memperoleh hasil yang lebih rendah yaitu 60C-130C. Terjadinya perubahan greenery dan agroklimat serta penurunan suhu disebabkan karena adanya fenomena atmosfer yaitu la-nina (penurunan suhu). Selanjutnya berdasarkan uji korelasi terdapat hubungan antara greenery dengan agroklimat pada selang kepercayaan 1% antara NDVI dan LSTyang bernilai positif dan sangat kuat.